Ficus longistipulata - Tsen, S.; Felix, E. C.; Damit, A.; Khoo, E.; Matusin, D.; Colin Ruzelion Maycock; Mohd Yusof, Nur Adillah, M.Y.; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Ficus longistipulata is endemic to Sabah, Malaysia. It is only known from Danum Valley, Lahad Datu. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2. The species does not experience continuing decline as it is in a well protected area. The most plausible threat that can affect the population of this species is climate change. If this was to occur it could drastically change the conservation status of this species towards Critically Endangered or Extinct. This species is assessed as Vulnerable. Ficus longistipulata is endemic to Sabah, Malaysia. It is only known from Danum Valley, Lahad Datu.